2015
DOI: 10.1021/acs.joc.5b01348
|View full text |Cite
|
Sign up to set email alerts
|

5,20-Di(pyridin-2-yl)-[28]hexaphyrin(1.1.1.1.1.1): A Stable Hückel Antiaromatic Hexaphyrin Stabilized by Intramolecular Hydrogen Bonding and Protonation-Induced Conformational Twist To Gain Möbius Aromaticity

Abstract: 5,20-Di(pyridin-2-yl)-[28]hexaphyrin(1.1.1.1.1.1) 7 was prepared and characterized as a stable Hückel antiaromatic molecule with a dumbbell-like structure stabilized by effective intramolecular hydrogen bonding interactions involving the 2-pyridyl nitrogen atoms. Pd(II) metalation of 7 afforded two bis-Pd(II) complexes, 9-syn and 9-anti, whose structures are rigidly held by Pd(II) coordination, rendering 9-syn to be nonaromatic because of its highly distorted structure and 9-anti to be Hückel antiaromatic beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 30 publications
(22 reference statements)
3
13
0
Order By: Relevance
“…Along with the different geometries between 1 and 2, they showed contrasting magnetic shielding effect and harmonic oscillator model of aromaticity (HOMA) values (Figures S4-S6 and Table S1), [45][46][47] which were well matched with the aromatic and anti-aromatic character of 1 and 2, respectively. 30 Similar geometrical differences was observed for other aromatic and anti-aromatic porphyrinoid congeners, [48][49][50][51][52][53] which illustrates the relationship between the aromaticity and molecular structure in that the inherent instability of the anti-aromatic nature generates distorted and asymmetric structures for energetic stabilization, in contrast with the stable planar conformations of aromatic molecules for effective p conjugation. [2][3][4][5][6]45 The opposite geometries were observed in the S Q state; the planar symmetric structure of 1 in the S 0 state became distorted and asymmetric in the S Q state, whereas the distorted structure of 2 became more planar and symmetric ( Figure 3).…”
Section: Resultssupporting
confidence: 56%
“…Along with the different geometries between 1 and 2, they showed contrasting magnetic shielding effect and harmonic oscillator model of aromaticity (HOMA) values (Figures S4-S6 and Table S1), [45][46][47] which were well matched with the aromatic and anti-aromatic character of 1 and 2, respectively. 30 Similar geometrical differences was observed for other aromatic and anti-aromatic porphyrinoid congeners, [48][49][50][51][52][53] which illustrates the relationship between the aromaticity and molecular structure in that the inherent instability of the anti-aromatic nature generates distorted and asymmetric structures for energetic stabilization, in contrast with the stable planar conformations of aromatic molecules for effective p conjugation. [2][3][4][5][6]45 The opposite geometries were observed in the S Q state; the planar symmetric structure of 1 in the S 0 state became distorted and asymmetric in the S Q state, whereas the distorted structure of 2 became more planar and symmetric ( Figure 3).…”
Section: Resultssupporting
confidence: 56%
“…It should be pointed out that up to four reductions have also been reported for other metallohexaphyrins containing different substituents and different central metal ions [11,21,23,25,47]. The potentials of these processes are summarized in Table S1, while structures of the previously examined metallohexaphyrins are shown in Fig.…”
Section: Electrochemistrymentioning
confidence: 88%
“…Also shown in Chart 1 are structures of a recently investigated series of mono-copper tripyrrinones, represented as (Ar) 3 TPO 2 Cu, where TPO 2 is a dianion of the tripyrrinone and Ar is a 4-CH 3 OPh, 4-CH 3 Ph, Ph or 4-ClPh substituent [46] and the related mono-metallic porphyrins with the same central metal ions and meso-substituents as in the case of HexaPyM 2 . A number of metallohexaphyrins have been characterized in the solid state and in solution [10-14, 16, 20, 21, 25, 47], but not a great deal is known about their electrochemical and spectroelectrochemical properties [11,21,25,47]. This is addressed in the current manuscript where redox properties of a bis-copper and bis-zinc hexaphyrin are examined and the data for the bis-Cu(II) compound compared not only with that for a related mononuclear copper(II) porphyrin having the same mesosubstituents but also with a recently described monocopper(II) tripyrrinone [46] which has three pyrrole units and a structure that corresponds to approximately one half the structure of HexaPyCu 2 as shown in Chart 1.…”
Section: Introductionmentioning
confidence: 99%
“…As the representative examples, free base [28]hexaphyrins can adopt various conformation including dumbbell, rectangular, Figure‐of‐eight, Möbius strip‐like, and triangular shapes . In recent years, we have reported that free base [28]hexaphyrins become stable antiaromatic molecules with dumbbell conformations when they carry meso ‐substituents such as 1‐alkyl‐2‐imidazolyl, pyridin‐2‐yl, and benzoyl, which act as a hydrogen bonding acceptor toward the inner‐directing pyrrolic protons. As an extension of these works, we report here the synthesis of 5,20‐bis(ethoxycarbonyl)‐10,15,25,30‐tetrakis(pentafluorophenyl) [28]hexaphyrin(1.1.1.1.1.1) 3 and its bis‐Ni II and bis‐Cu II complexes.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Mosto fe xpanded porphyrins are conformationally flexible, whicha re different from planar porphyrins. As the representative examples, free base [28]hexaphyrins can adopt various conformation including dumbbell, [2][3][4] rectangular, [5]…”
mentioning
confidence: 99%